Adalimumab, Infliximab, and Vedolizumab in Treatment of Ulcerative Colitis: A Long-Term Retrospective Study in a Tertiary Referral Center. Issue 4 (13th July 2021) - Gagnon, Ann-Lorie; Beauchesne, William; Tessier, Laurence; David, Charles; Berbiche, Djamal; Lavoie, Alexandre; Michaud-Herbst, Alban; Tremblay, Karine
Abstract: Background: Biological therapies have changed the landscape of pharmacological management of ulcerative colitis (UC). However, a large proportion of patients do not respond to biologics, lose their response over time, or present adverse drug events. This study aims to assess therapeutic response and treatment persistence to adalimumab, infliximab, and vedolizumab, 3 agents widely used in a tertiary referral center of Saguenay–Lac-Saint-Jean (Quebec, Canada). Methods: We conducted a retrospective population-based study with a thorough review of patients' medical charts. Adults at UC diagnosis, with current or past use of adalimumab, infliximab, or vedolizumab, were included in the study. Clinical data were collected in order to assess response phenotypes and persistence to treatment. Kaplan–Meier curves were performed to assess treatment persistence, and predictors for discontinuation were assessed using Cox regression analyses. Results: A total of 134 patients were included in this study. For the cases exposed to adalimumab, infliximab, and vedolizumab, 56.9%, 62.5%, and 47.5% were responders, respectively. Mean persistence rates (95% CI) were 5.5 (4.3–6.6), 10.1 (8.7–11.5), and 3.6 (2.9–4.2) years for adalimumab, infliximab, and vedolizumab, respectively. Increased persistence rates were observed in biologic-naïve patients treated with infliximab in comparison to those with the previous exposition to 2 biologics, but no such effect was observed for adalimumab or vedolizumab. Overall, 61.9% of cases had adverse drug events and of these, 6 led to treatment discontinuation. Conclusion: This study presents long-term treatment persistence data with adalimumab, infliximab, and vedolizumab, showing that more than half of cases treated with these biologics remained on treatment at least 24 months after initiation. Lay Summary: We present a first population-based retrospective cohort that collected longitudinal data studying 3 of the most used biologics for the treatment of ulcerative colitis in Canada, including data on therapeutic response phenotypes and treatment persistence.